Modelagem de nicho em espécies de plantas do Cerrado e distribuição espacial da variabilidade genética - CAVALCANTI, Fábio André Gomes S (2010)
Ecological and evolutionary factors may explain the patterns of intrapopulation variability across the geographic distribution of a species. More suitable habitats, in ecological terms, allow the survival of greater number of individuals, which increases the genetic variability in the population, while in less suitable habitats, because of smaller population size, individuals have lower reproductive rate and higher mortality rate, these populations may lead to loss of genetic variability and extinction. In this context, the goal of this study was to use meta-analysis techniques to relate the genetic variables (observed and expected heterozygosity and inbreeding) with the models of potential geographical distribution of nine species of Cerrado plants. In addition, genetic variables were correlated with human occupation at sites where plant species occurred. For this work were used 11 studies, in which genetic data were obtained from literature and the points of occurrence in databases and also the literature. Five species distribution models (Maxent, Mahalanobis, Euclidian, Domain and Bioclim) were used and then superimposed on a combined basis (i.e Ensemble forecasting). Were performed Pearson correlations between genetic variables and environmental and human occupation. The coefficients of these correlations were matched using a meta-analysis to find a general correlation studies. The correlations between genetic variables with the ecological variable (i.e environmental suitability) and human occupation tended to zero. Although significant values have been obtained with studies of isozymes for the human index (r = 0.57 P = 0.01) related, independent, with the observed heterozygosity. A positive relationship exists between the human and the expected heterozygosity index (r = 0.27, P = 0.01) was found in the relationship between all the studies together. We also found significant values for studies with isoenzymes in ecological indices (r = 0.39, P = 0.04) and human (r = 0.50, P = 0.01) and the distance from the center of the potential distribution species (r = -0.44, P = 0.05) between the expected heterozygosity. The results of the mean effect between heterozygosity and occupation indices suggest that the plants were evaluated in studies with isozymes show a high heterozygosity in places with high human occupation. Due to the occupation of the Cerrado be intense, but recent, and due to plant species have long life cycles of species populations may not yet be genetically structured in this new landscape of the Cerrado. The results of studies with isozymes, correlation between heterozygosity and distance from the center of potential distribution of species have confirmed our predictions. Plants tend to lose more distant genetic variability by having a lower population density. The relationship between habitat suitability and distance from the center indicated a relationship is also negative (r = -0.35, P <0.05), suggesting that adequacy is also lower in peripheral regions. In general, the methodology used to conduct preliminary assessments of the distribution of the population structure of Cerrado plants related to genetic variables proven very useful and practical.